2014
DOI: 10.1371/journal.pone.0100950
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Expression of the Retinoblastoma Protein Shows That the Related Signaling Pathway Is Essential for Mediating the Antineoplastic Activity of Erufosine

Abstract: Erufosine is a new antineoplastic agent of the group of alkylphosphocholines, which interferes with signal transduction and induces apoptosis in various leukemic and tumor cell lines. The present study was designed to examine for the first time the mechanism of resistance to erufosine in malignant cells with permanently reduced expression of the retinoblastoma (Rb) protein. Bearing in mind the high number of malignancies with reduced level of this tumor-suppressor, this investigation was deemed important for u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…Erufosine interferes with survival signals (Chometon, et al, 2014), and interacts with the 18 kDa mitochondrial translocator protein leading to activation of the mitochondrial apoptosis cascade (Veenman, et al, 2014). The retinoblastoma signaling pathway has been shown to be essential for mediating the antitumor activity of erufosine, and hence its efficacy might be predicted by determining the retinoblastoma protein status (Zaharieva, et al, 2014;Zaharieva, et al, 2007). Both in vitro and in vivo assays have shown promising antitumor activity of erufosine alone and in combination with radiation on astrocytoma and glioblastoma cell lines (Awde, et al, 2013;Rubel, et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Erufosine interferes with survival signals (Chometon, et al, 2014), and interacts with the 18 kDa mitochondrial translocator protein leading to activation of the mitochondrial apoptosis cascade (Veenman, et al, 2014). The retinoblastoma signaling pathway has been shown to be essential for mediating the antitumor activity of erufosine, and hence its efficacy might be predicted by determining the retinoblastoma protein status (Zaharieva, et al, 2014;Zaharieva, et al, 2007). Both in vitro and in vivo assays have shown promising antitumor activity of erufosine alone and in combination with radiation on astrocytoma and glioblastoma cell lines (Awde, et al, 2013;Rubel, et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Erufosine is a third-generation alkylphosphocholine with remarkable antineoplastic properties [30,31,32,33]. Its efficacy is related to changes in the expression of certain components of vital signaling pathways (for review see [34]).…”
Section: Discussionmentioning
confidence: 99%
“…We found that FHIT and CDKN1B, known as haploinsufficient tumor suppressors (24,34,35), were significantly upregulated in MDA-PCa-2b cells upon miR-130b inhibition and luciferase reporter assay showed that both genes are a direct miR-130b target. A previous study found that stimulation of CDKN1B caused G 2 arrest by repressing cyclin D3 (36). In non-small cell lung cancer (NSCLC), SIRT1 silencing suppresses proliferation and induces senescence in a CDKN1B (p27Kip1)-dependent manner (37).…”
Section: Discussionmentioning
confidence: 99%